Construction accounting and financial management - Coombs, William E.; Palmer, William J. (New York : McGraw Hill Education, 1977)
Although accounting principles tend to remain the same it is reasonable to say that their application to any particular industry, and to any specific business in that industry, usually requires careful analysis and sound judgment. This statement is certainly true of the construction industry. This book cannot take the place of detailed information nor of the experience with individual problems of any particular construction company. It can, however, survey the problems peculiar to the construction industry and indicate how to apply standard accounting techniques to arrive at sound solutions. With operating conditions so varied and the individual contractor's circumstances likely to be so complex, it is often necessary to go back and review basic accounting and business principles in relation to the specific conditions in a given company before management can use accounting as a true operational tool. It is for this reason that this book is devoted more to the "why" than to the "how" of construction accounting. Certainly, among the techniques described, the experienced accountant will find few, if any, that are basically unfamiliar to him, but he may see them applied in ways that may be somewhat unexpected.
1. Basic Operational Patterns -- 2. Basic Accounting Patterns -- 3. Centralized or Decentralized Accounting -- 4. Pre-job Procedures -- 5. Purchasing Policies and Procedures -- 6. Subcontracting Policies and Procedures -- 7. Change Order Routines -- 8. Accounting for Labor -- 9. Accounting for Materials and Supplies -- 10. Accounting for Equipment Costs -- 11. Accounting for Subcontract Costs -- 12. Accounting for Distributable Costs -- 13. Vouchering and Disbursement Control -- 14. Accounting for Contract Revenue and Cash Receipts -- 15. General and Subsidiary Ledgers -- 16. Financial and Cost Reporting -- 17. Internal Auditing -- 18. Camp, Mess Hall, Commissary, and Protective Functions -- 19. Insurance Problems and Job Accounting -- 20. Forms and Printing in Job Accounting and Reporting -- 21. Effect of Personnel Policies on Job Accounting and Reporting.
Includes index.
Keywords: FINANCIAL ACCOUNTING